Black Metal’s Apophatic Curse - Scott, Niall (Théologiques, 2018)
Black metal uses negative language and negation as affirmation in the opposite direction to the Christian mystical tradition. Here, I argue that black metal completes the direction of negation to its proper conclusion in a turning away from God rather than using negative language to eulogise God. My first claim is that all worship is a form of curse, where negative theology demonstrates the inadequacy of language in its attempt to attest to the very thing it aims to affirm. I maintain that black metal demonstrates a consistency in apophatic thought where the mystical approach of Pseudo Denys and Meister Eckhart fail. Applying Milem’s desire theory and renunciation theory, and using lyrics from black metal bands, I argue that rather than negating the self, black metal’s apophatic approach reaffirms the self’s material existence in opposition to God. The affirmation rooted in negation of the bounded physical nature of humanity is the source from which a curse against the Christian God emanates.